Management Patterns of Hepatic Encephalopathy: A Nationwide Survey in India - Sharma, Praveen (J Clin Exp Hepatol, 2015)
INTRODUCTION AND AIM: Hepatic encephalopathy (HE) is a common complication of cirrhosis. There is no standard practice for its management. This survey was done to determine the diagnostic and therapeutic practices of physicians treating patients with HE in patients with cirrhosis. MATERIAL AND METHOD: We designed a 21-item questionnaire, which was given to physicians working in academic and non-academic institutes and regularly treating patients with HE. RESULTS: Of 500 printed questionnaires, we received 451 questionnaires [323 (72%) general physicians and 128 (28%) gastroenterologists] from academic and non-academic institutes. Commonest precipitating event of HE was upper gastrointestinal bleed (47%), constipation (18%) and spontaneous bacterial peritonitis (12%). Arterial ammonia was always measured at admission by 156 (35%) physicians, never measured by 128 (28%) and sometimes by 167 (37%). Prophylactic antibiotics were used by 54% of physicians on the day of admission irrespective of any precipitating event, and 13% used antibiotics only if cultures were positive while others used antibiotics only if patient needs intubation or had variceal bleed as the cause of precipitation of HE. Disaccharides remained the mainstay of treatment in the management of HE and were always used by 87% (n = 391) followed by LOLA (n = 297, 66%) and rifaximin (n = 276, 61%). Combination of therapy was used by 84% of respondents. Lactulose enema was used in patients with HE by 280 (62%) physicians and was thought to be as good as giving lactulose by mouth or nasogastric tube in the treatment of HE. Regarding the recovery of HE with the present mode of therapy, of 451 responses, only 11% (n = 49) got 90–100% response to present therapy for the recovery of HE, while 70–90% response was seen by n = 152 (34%) and 50–70% response was seen by n = 183 (41%). Lactulose was prescribed as secondary prophylaxis agent more by gastroenterologists than non-gastroenterologists (76% vs 41%, P = 0.001). Similarly, rifaximin was more prescribed by gastroenterologists at discharge compared to non-gastroenterologists (32% vs 17%, P = 0.001). CONCLUSION: Non-absorbable disaccharides are the most commonly prescribed treatment for HE and for secondary prophylaxis of HE. Combination of therapy (lactulose and LOLA or lactulose and rifaximin) was commonly used by treating physicians.